A Space Domain Energetics Study for CO2 Increasing Based on SRES-A2 Emission Scenario - José Augusto P. Veiga; Tercio Ambrizzi; Alexandre B. Pezza (Advances in Meteorology)
This work presents a detailed investigation of the changes in the global pattern of energetics under a prescribed temporal evolution of CO2 concentration as proposed by the A2 IPCC forcing scenario (SRES-A2) using a combination of reanalysis and climate models. A validation climatology is computed using the classic Lorenz energetic formulation, with generation and dissipation components estimated as residuals. The results show a good agreement overall between models and reanalysis for the present day climate, noting that the models generally give more zonal energy and less eddy energy when compared to the reanalysis. Spatial analysis translates the above results as models depicting greater energy associated with the subtropical jet streams than effectively observed. This pattern is observed regardless of season or hemisphere. The projections for future climate scenarios suggest a further increase in the zonal kinetic energy, with a slight average reduction in all other terms. This pattern is seen in association with a substantial decrease in the conversion term mainly associated with sensible heat transport (CA) under a warmer climate. In agreement with recent work in the literature, our results suggest an overall reduction of the global energetics under increasing CO2.